The Correlation between Teachers' Beliefs and Their Professionalism - Zaiyana Putri; Marisa Yoestara; Zulfadli A. Aziz; Yunisrina Qismullah Yusuf (Proceedings of AICS - Social Sciences, 2017)
Teachers’ beliefs are one of the most important components that may impact the teachers’ competency. This article aims to find out how far the impact of teachers’ beliefs on their motivation to be employed in professional developments, including teacher’s training. This research was conducted in Pidie District, Aceh, with the total sample of 68 English teachers (from SMA and SMK), of both civil servants and non-civil servants. This research is a qualitative descriptive research using questionnaire and interview as the instruments to obtain data. The data was analyzed by using the Spearman correlation (r). Based on the results of the study, it is found that the teachers’ beliefs and their motivation to actively participate in professional development activities have positive correlations. Keywords:teachers’ beliefs, English teacher, professional development.